Composition and variability of US soybean meal intended for swine diets - Collier, Sierra (My University, 2026)
Soybean meal (SBM) is the predominant plant-based protein source used in swine diets because of its favorable amino acid profile, high nutrient digestibility, widespread availability, and relatively low cost. However, SBM contains antinutritional factors, including trypsin inhibitor, and its nutritional value may vary because of differences in soybean composition, processing conditions, and analytical methodology. Therefore, the objectives of this thesis were to evaluate the effects of increasing dietary trypsin inhibitor units (TIU) on nursery pig growth performance and nutrient digestibility, characterize the composition and variability of SBM produced by US soybean processing plants, and quantify analytical variation within and between laboratories when measuring SBM composition and variability. To address the effects of trypsin inhibitor on growth performance, 360 nursery pigs were used in a 42-d growth trial to evaluate the effects of increasing dietary TIU across six treatments ranging from 1.4 to 4.9 TIU/mg of complete feed. Soy flour (76 TIU/mg) was added at the expense of SBM (5 TIU/mg) to create experimental diets. Increasing dietary TIU decreased average daily gain, average daily feed intake, and gain:feed ratio during all three dietary phases and overall, resulting in a 5.6 kg reduction in final body weight from the lowest to greatest TIU concentration. Increasing TIU also reduced the apparent total tract digestibility of crude protein. Based on the SBM inclusion rates used in this experiment, SBM containing greater than approximately 6 TIU/mg has the potential to decrease nursery pig growth performance and nutrient digestibility. To address the chemical composition of SBM, 271 samples were collected from 29 US soybean processing plants at two timepoints within the same crop year. Samples were analyzed for nutrient composition, processing quality indicators, and physical characteristics. Soybean meal composition was relatively consistent between sampling timepoints; however, processing method influenced several compositional and quality characteristics. Solvent extracted SBM contained greater crude protein, but lower ether extract and TIU than extruded-expelled SBM. Considerable variation within and between processing plants was observed for ether extract, calcium, TIU, potassium hydroxide protein solubility, protein dispersibility index, and particle size, whereas crude protein, amino acid concentrations, and fatty acid profiles were comparatively consistent. In a companion study of the soybean meal composition experiment, SBM samples from 27 soybean processing plants were collected to evaluate analytical variation between and within laboratories for proximate composition, neutral detergent fiber (NDF), Ca, P, trypsin inhibitor, and amino acid profile. Samples were analyzed in quadruplicate at four laboratories. Dry matter and crude protein exhibited the lowest analytical variation and demonstrated strong repeatability within laboratories and reproducibility between laboratories. Ether extract, NDF, select amino acids, and trypsin inhibitor exhibited greater variation between laboratories. In conclusion, these studies establish the negative effects of increasing dietary TIU on nursery pig growth performance and nutrient digestibility, provide an updated benchmark of US SBM composition and variability, and demonstrate the importance of laboratory and analytical method selection when interpreting SBM quality measurements.
Keywords: analytical variation; antinutritional factors; soybean meal quality; soybean processing; trypsin inhibitor; weanling pigs